(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article aims to make brief considerations about the transition rules for retirement, resulting from the social security reform made by Constitutional Amendment No. 103/2019. Initially, a brief historical review of social rights is presented. Next, each of the transition rules provided for in articles 15, 16, 17, 18 and 20 of the aforementioned Constitutional Amendment are addressed separately. Finally, we discuss the value of the initial monthly income of the benefits granted based on the aforementioned rules of transition.